Preparation method of lignin functionalized carbon nanofiber electrode material and application of lignin functionalized carbon nanofiber electrode material in all-vanadium redox flow battery

By introducing lignin into vanadium battery electrode materials and using electrospinning technology to prepare carbon nanofiber electrode materials, the problem of insufficient performance of electrode materials under high current density is solved, the electrochemical reaction activity and wettability is improved, and the further development is achieved. Efficient battery performance and cycle life.

CN119121456APending Publication Date: 2024-12-13LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311629983.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing vanadium battery electrode materials lack electrochemical performance under high current density, resulting in battery polarization and cycle life problems, and lack efficient electrochemical reactivity and wetting properties.

Method used

By introducing lignin into carbon fiber electrode materials, electrospinning technology is used to prepare lignin-functional carbon nanofiber electrode materials, which enhances the mechanical strength and electrochemical catalytic activity of the fibers, and forms a multi-stage hydrogen bond network and nano-scale pore structure. Increase the specific surface area and electrocatalytic activity of the electrode.

Benefits of technology

It significantly improves the electrochemical reaction area and catalytic activity of the electrode, improves the mass transfer rate of the electrolyte and the battery performance, extends the stable running time of the battery, and realizes the high value-added utilization of biological waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121456A_ABST
    Figure CN119121456A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lignin functionalized carbon nanofiber electrode material and application of the lignin functionalized carbon nanofiber electrode material in an all-vanadium redox flow battery. The method comprises the following steps: adding a proper amount of lignin into a mixed solution of polyacrylonitrile (PAN) and N, N-dimethylformamide (DMF) to obtain an electrospinning precursor solution lignin / PAN / DMF containing lignin; the preparation method comprises the following steps: carrying out electrostatic spinning by adopting an electrostatic spinning technology to obtain original electrospun nanofibers, sequentially carrying out pre-oxidation on the obtained original nanofibers in an air atmosphere and carrying out carbonization treatment in a nitrogen atmosphere to obtain the lignin functionalized carbon nanofiber electrode material, and applying the lignin functionalized carbon nanofiber electrode material to an electrode material of an all-vanadium redox flow battery. And the battery performance can be effectively improved. The high-activity biomass carbon nanofiber prepared by the preparation method disclosed by the invention can simultaneously have high electrochemical activity surface area and high electrochemical catalytic activity, so that the high-activity biomass carbon nanofiber can meet the actual application requirement of a high-power density electric pile. The method is simple, high in controllability and excellent in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and energy storage, and specifically relates to a preparation method of a lignin-functionalized carbon nanofiber electrode material and its application in an all-vanadium liquid flow battery. Background Art

[0002] As the demand for non-renewable resources such as fossil fuels continues to increase, ensuring sustainable development while reducing carbon dioxide emissions has become an important issue. As a large-scale energy storage device with great development prospects, vanadium batteries have attracted widespread attention due to their long cycle life, large energy storage capacity, flexible design and green environmental protection.

[0003] As the site of electrochemical reactions in vanadium batteries, electrodes play a decisive role in the performance and cycle life of vanadium batteries. With the development of vanadium battery technology, the development of high-power vanadium battery stacks has become an important way to reduce energy storage costs, which also puts higher requirements on the electrochemical performance of electrodes at high current densities. Therefore, designing and preparing high-performance advanced electrode materials, further reducing battery polarization, and ensuring stable operation of batteries at high current densities have become prerequisites for the development of the next generation of vanadium battery stacks.

[0004] In recent years, electrospinning technology with strong controllability and simple operation has been widely used to regulate the microstructure of carbon fiber electrode materials to improve the performance of liquid flow batteries. Electrospun carbon nanofiber (ECNFs) electrodes have a higher specific surface area than commercial carbon felt electrodes, but their wettability and electrochemical reaction activity still need to be improved. Optimizing the composition of electrode materials can improve the electrochemical reaction activity of electrode materials while improving hydrophilicity, such as introducing specific heteroatom groups and catalytically active transition metal oxides on the surface of carbon electrodes. Using simple and controllable electrospinning technology, by introducing functional biomass component lignin into the precursor solution, thanks to the rich oxygen-containing functional groups of lignin, the carbon fiber material can be given good surface hydrophilicity and catalytic activity while enhancing the fiber strength, thereby effectively improving the electrochemical reaction area and electrocatalytic activity of the electrode material. Using it as a liquid flow battery electrode material can effectively improve the mass transfer rate of the electrolyte in the electrode and the electrochemical reaction rate on the electrode surface, thereby improving the battery performance. In addition, as an economical and environmentally friendly biomass material, the application of lignin in electrochemical energy storage electrode materials can further broaden its application areas and achieve high value-added utilization of biological waste. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a lignin-functionalized highly active carbon nanofiber electrode material. The material can improve the strength of carbon fibers while increasing their electrochemical active area and electrochemical catalytic activity, which is expected to further improve the performance of vanadium batteries.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a lignin-functionalized carbon nanofiber electrode material comprises the following steps:

[0008] 1) adding lignin to a mixed solution of polyacrylonitrile (PAN) and N,N-dimethylformamide (DMF) to obtain an electrospinning precursor solution containing lignin, lignin / PAN / DMF;

[0009] 2) using electrospinning technology to perform electrospinning to obtain electrospun nanofibers containing original lignin;

[0010] 3) pre-oxidizing the obtained original electrospun nanofibers containing lignin to obtain pre-oxidized nanofibers;

[0011] 4) The pre-oxidized nanofibers are carbonized to obtain lignin-functionalized carbon nanofiber electrode materials.

[0012] Furthermore, in the above preparation method, in step 1), the molecular weight of the polyacrylonitrile PAN is 60,000 to 150,000.

[0013] Furthermore, in the above preparation method, in step 1), the lignin is dealkalized lignin.

[0014] Furthermore, in the above preparation method, in step 1), in the mixed solution of lignin, polyacrylonitrile PAN and N,N-dimethylformamide DMF, the concentration of polyacrylonitrile PAN is 10-18wt%, and the concentration of lignin is 0.6-1wt%.

[0015] Furthermore, in the above preparation method, in step 1), the conditions for mixing lignin, polyacrylonitrile PAN and N,N-dimethylformamide DMF are controlled as follows: temperature is 70-90° C., and magnetic stirring is performed for 12-24 hours.

[0016] Furthermore, in the above-mentioned preparation method, in step 2), the conditions for the electrospinning are: the receiver is a roller; the voltage is 15-20 kV; the receiving distance is 10-15 cm; the nozzle moving distance is 0-40 mm; the nozzle moving speed is 5-15 mm / s; the spinning temperature is 25-40°C; the spinning humidity is 30-50% RH; the push speed is 10-50 μL / min; and the spinning time is 1-10 h.

[0017] Furthermore, in the above-mentioned preparation method, in step 3), the conditions of the pre-oxidation treatment are: heat treatment at 250-300° C. for 0.5-2 h in an air atmosphere.

[0018] Furthermore, in the above-mentioned preparation method, in step 4), the conditions of the carbonization treatment are: heat treatment at 900-1200° C. for 1-3 hours in vacuum, nitrogen or inert atmosphere.

[0019] Application of the lignin-functionalized carbon nanofiber electrode material prepared by any of the preparation methods described above in all-vanadium liquid flow batteries.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention proposes to utilize a large number of hydroxyl and carboxyl groups in the lignin structure to form a multi-level hydrogen bond network with polyacrylonitrile-based fibers, thereby reducing fiber breakage during heat treatment and improving the mechanical strength of carbon fiber materials.

[0022] 2. The oxygen atoms in lignin will be doped into carbon nanofibers as active sites, thereby improving the wettability and electrocatalytic activity of electrode materials.

[0023] 3. The application of lignin in biowaste in the field of new materials has important social and economic significance.

[0024] 4. The present invention utilizes the controllability of electrospinning technology and combines the functionality of lignin to prepare a new type of high-performance carbon nanofiber electrode material. It is easy to obtain a series of lignin-functionalized carbon nanofiber materials with different composition and structural characteristics, and optimize the materials for different application conditions. The method is flexible and universal. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Scanning electron microscope photos of the blank polyacrylonitrile carbon nanofiber electrode material (a) and the lignin-functionalized carbon nanofiber electrode material (b) prepared in Example 1.

[0026] Figure 2 Cyclic voltammetry curves of blank polyacrylonitrile carbon nanofiber electrode material and lignin-functionalized carbon nanofiber electrode material prepared in Example 1 in vanadium electrolyte (scan rate: 5 mV·s -1 ).

[0027] Figure 3 Polarization curves of single cells assembled using the blank polyacrylonitrile carbon nanofiber electrode material and the lignin-functionalized carbon nanofiber electrode material prepared in Example 1 as electrode materials, respectively.

[0028] Figure 4 The single cell assembled with the blank polyacrylonitrile carbon nanofiber electrode material and the lignin-functionalized carbon nanofiber electrode material prepared in Example 1 as electrode materials was tested at 200 mA·cm -2 The charge and discharge curve diagram below.

[0029] Figure 5 The coulombic efficiency CE, voltage efficiency VE and energy efficiency EE of a single cell assembled with the blank polyacrylonitrile carbon nanofiber electrode material and the lignin-functionalized carbon nanofiber electrode material prepared in Example 1 as electrode materials at different current densities. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0031] Example 1

[0032] (I) Comparative Example - Preparation of Blank Polyacrylonitrile Carbon Nanofiber Electrode Material

[0033] 1) After drying polyacrylonitrile (PAN) powder with a molecular weight of 150,000, it was mixed with N,N-dimethylformamide (DMF) solution and magnetically stirred at 80°C for 10 hours until it was completely dissolved to obtain a mixed solution of polyacrylonitrile and N,N-dimethylformamide (PAN / DMF solution) with a polyacrylonitrile mass percentage concentration of 12 wt%, which was used as an electrospinning precursor solution.

[0034] 2) Put the electrospinning precursor solution into a syringe and place it on a syringe pump, connect the pipeline, and perform electrospinning. Electrospinning conditions: voltage 20kV; roller as fiber receiver; distance between stainless steel flat needle and receiver 10cm; nozzle moving speed 10mm / s; nozzle moving distance 30mm; spinning temperature 30℃; spinning humidity 40% RH; push speed 25μL / min; spinning time 2h. After setting the electrospinning parameters, start electrospinning to obtain blank polyacrylonitrile electrospun nanofibers.

[0035] 3) Pre-oxidation treatment: The obtained blank polyacrylonitrile electrospun nanofibers were heat treated at 290° C. for 1 h in an air atmosphere.

[0036] 4) Carbonization treatment: The sample after pre-oxidation treatment was heat treated at 1000° C. for 2 h in a nitrogen atmosphere, and after cooling, a blank polyacrylonitrile carbon nanofiber electrode material was obtained.

[0037] (II) Preparation of highly active lignin-functionalized carbon nanofiber electrode materials

[0038] 1) According to the mass ratio of lignin: polyacrylonitrile = 1:15, dried polyacrylonitrile (PAN) powder with a molecular weight of 85,000 and lignin powder were dissolved in N,N-dimethylformamide (DMF) solvent, and magnetically stirred at 80°C for 12 hours until completely dissolved to obtain an electrospinning precursor solution of lignin / PAN / DMF with a mass percentage of polyacrylonitrile of 12 wt%.

[0039] 2) The electrospinning precursor solution containing lignin (lignin / PAN / DMF) was sucked into the injector of the electrospinning equipment, and the pipeline was connected to perform electrospinning. The electrospinning conditions were as follows: voltage of 20 kV, the roller was a fiber receiver, the receiving distance was 10 cm, the nozzle moving speed was 10 mm / s, the nozzle moving distance was 30 mm, the propulsion speed was 25 μL / min, the temperature was 30 ° C, the humidity was 40 RH%, and the spinning time was 2 h, and the original electrospun nanofibers containing lignin were obtained.

[0040] 3) Pre-oxidation treatment: The obtained original electrospun nanofibers containing lignin were heat treated at 290° C. for 1 h in an air atmosphere.

[0041] 4) Carbonization treatment: The pre-oxidation sample was heat treated at 1000° C. for 2 h in a nitrogen atmosphere to finally obtain a highly active lignin-functionalized carbon nanofiber electrode material.

[0042] Depend on Figure 1 As shown in b, the diameter of the prepared highly active lignin functionalized carbon nanofiber electrode material is about 200-300nm, and the fiber surface contains nanoscale pores of varying sizes, indicating that the electrode has a large specific surface area, which helps to improve the electrochemical reaction activity of the electrode. In addition, the fibers overlap each other to form a three-dimensional network structure, and at the same time form micron-sized macropores, providing a path for mass transfer of the electrolyte.

[0043] Example 2 Electrochemical performance of lignin-functionalized carbon nanofiber electrode materials

[0044] Method: A three-electrode system was used, with 1 cm prepared in Example 1. 2 Blank polyacrylonitrile carbon nanofiber electrode material and lignin functionalized carbon nanofiber electrode material were used as working electrode, saturated calomel electrode was used as reference electrode, platinum sheet was used as counter electrode, 0.1M VOSO4+2.0M H2SO4 was used as electrolyte, and the electrochemical properties of the electrode were investigated by cyclic voltammetry.

[0045] like Figure 2 As shown in the figure, three pairs of redox peaks appeared on the lignin-functionalized carbon nanofiber electrode material, corresponding to V 4+ / V 5+ , V 3+ / V4+ and V 2+ / V 3+ The electrochemical redox process shows that the electrode material has excellent electrocatalytic activity for the redox reaction of vanadium ions; in addition, a larger reaction current is shown on the lignin-functionalized carbon nanofiber electrode material, indicating that the material has a larger electrochemical reaction area and better electrocatalytic activity.

[0046] Example 3 Battery performance of lignin-functionalized carbon nanofiber electrode materials

[0047] Method: The lignin functionalized carbon nanofiber electrode material prepared in Example 1 was used as the positive and negative electrode materials, and the area of ​​the working electrode was 2×2 cm 2 , Nafion 212 is an ion exchange membrane, 1.65MV 3.5+ +3.0M H2SO4 as electrolyte, assemble a single cell. The blank polyacrylonitrile carbon nanofiber electrode material prepared in Example 1 was used as the control group, the blank polyacrylonitrile carbon nanofiber electrode material was used as the positive and negative electrodes, and the area of ​​the working electrode was 2×2 cm 2 , Nafion 212 is an ion exchange membrane, 1.65MV 3.5+ +3.0M H2SO4 as electrolyte, assemble single cell. The charge and discharge cut-off voltages are 1.8V and 1.0V respectively. The polarization curve, charge and discharge curve and battery efficiency of the battery are shown in Figure 3-5 shown.

[0048] Figure 3 The lignin-functionalized carbon nanofiber electrode material showed a higher power density than the blank polyacrylonitrile carbon nanofiber electrode material. The highest peak power density of the lignin-functionalized carbon nanofiber electrode material was 689.45 W·cm -2 , while the blank polyacrylonitrile carbon nanofiber electrode material was only 599.22 W·cm -2 .

[0049] Figure 4 In 200mA·cm -2 The charge and discharge performance of the battery assembled with lignin-functionalized carbon nanofiber electrode material and the battery assembled with blank polyacrylonitrile carbon nanofiber electrode material were compared. In the voltage range of 0-0.5V, compared with the battery assembled with blank polyacrylonitrile carbon nanofiber electrode material, the battery assembled with lignin-functionalized carbon fiber electrode material has lower charge voltage and higher discharge voltage, and the charge and discharge curve is more stable. The results show that the lignin-functionalized carbon fiber electrode material exhibits better charge and discharge performance.

[0050] Figure 5In the figure, the coulombic efficiency CE, voltage efficiency VE and energy efficiency EE of the lignin functionalized electrospun carbon nanofiber electrode material at different current densities. The battery can still operate smoothly at high current density, and at 200 mA cm -2 The voltage efficiency and energy efficiency of the lower battery reached 81.43% and 79.34%, respectively.

Claims

1. A method for preparing a lignin-functionalized carbon nanofiber electrode material, It is characterized in that The steps include: 1) adding lignin to a mixed solution of polyacrylonitrile (PAN) and N,N-dimethylformamide (DMF) to obtain an electrospinning precursor solution containing lignin, lignin / PAN / DMF; 2) using electrospinning technology to perform electrospinning to obtain electrospun nanofibers containing original lignin; 3) pre-oxidizing the obtained original electrospun nanofibers containing lignin to obtain pre-oxidized nanofibers; 4) The pre-oxidized nanofibers are carbonized to obtain lignin-functionalized carbon nanofiber electrode materials.

2. The preparation method according to claim 1, It is characterized in that In step 1), the molecular weight of the polyacrylonitrile PAN is 60,000 to 150,000.

3. The preparation method according to claim 1, It is characterized in that In step 1), the lignin is dealkalized lignin.

4. The preparation method according to claim 1, It is characterized in that In step 1), in the mixed solution of lignin, polyacrylonitrile PAN and N,N-dimethylformamide DMF, the concentration of polyacrylonitrile PAN is 10-18 wt %, and the concentration of lignin is 0.6-1 wt %.

5. The preparation method according to claim 1, It is characterized in that In step 1), the mixing conditions of lignin, polyacrylonitrile PAN and N,N-dimethylformamide DMF are controlled as follows: temperature is 70-90° C. and magnetic stirring is performed for 12-24 hours.

6. The preparation method according to claim 1, It is characterized in that In step 2), the conditions for the electrospinning are: the receiver is a roller; the voltage is 15-20 kV; the receiving distance is 10-15 cm; the nozzle moving distance is 0-40 mm; the nozzle moving speed is 5-15 mm / s; the spinning temperature is 25-40°C; the spinning humidity is 30-50% RH; the pushing speed is 10-50 μL / min; and the spinning time is 1-10 h.

7. The preparation method according to claim 1, It is characterized in that In step 3), the pre-oxidation treatment conditions are: heat treatment at 250-300° C. for 0.5-2 h in an air atmosphere.

8. The preparation method according to claim 1, It is characterized in that In step 4), the carbonization treatment is carried out under the following conditions: heat treatment at 900-1200° C. for 1-3 h in vacuum, nitrogen or inert atmosphere.

9. Use of the lignin-functionalized carbon nanofiber electrode material prepared by the preparation method according to any one of claims 1 to 8 in an all-vanadium liquid flow battery.